«No tenía pretensiones, solo quería trabajar» Españolas en Francia, servicio doméstico y empleo informal (1939-1975) - Rocío Negrete Peña (Cahiers de Civilisation Espagnole Contemporaine)
Domestic service and work done at home are two economic fields highly feminised and largely occupied by migrants. Due to triple discrimination and lack of recognition, any academic discipline (excepting sociology) doesn’t have studied enough this work done by migrant women. Spanish women who had migrated, because of both political (1939) or economic (from 1956) reasons, worked as domestic, as well as in informal activities. Housekeepers, Jacks of all Trades, maids, dressmakers working from home, these women configured an important part of their identity by means of their work. And, their work has been, at the same time, a useful tool for their emancipation from the social, economic and politic point of view.